ANALISIS PEMAHAMAN KONSEP PERBANDINGAN BERBALIK NILAI DITINJAU DARI JENIS KELAMIN: Analysis Of Understanding Of The Concept Of Invers Comparison In Terms Of Gender - Pembeu, Mega Cendrakasih; Pathuddin, Pathuddin; Nurhayadi, Nurhayadi; Paloloang, Baharuddin (Aksioma, 2024)
This study aimed to describe an analysis of the understanding of the concept of inverse comparison in terms of gender differences. The subjects of this research were 4 students in Class VIII of St Paul's Catholic Middle School, Palu, namely high ability students, male LA and female FA and low ability students, male IY and female MG. This type of research uses case study research with a qualitative approach. Data collection was carried out by giving assignments and interviews. The results of this research show that the ability to understand concepts is grouped based on indicators of concept understanding, namely the ability to restate a concept, the ability to present a concept in the form of a mathematical representation, and the ability to select, utilize and use certain procedures. LA students meet all indicators of concept understanding, FA students meet 2 indicators, IY and MG students are less able to meet all indicators. These results show that male students' conceptual understanding is higher than female students.